THE MAKING OF TECHNOLOGICAL MAN (Author: John Hubbel Weiss) - Gradwell, John (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1982)
John Hubbel Weiss. THE MAKING OF TECHNOLOGICAL MAN. Cambridge, Massachusets: Massachusetts Institute of Techno1ogy, 1982. 377 pp. $30.00.